1992
DOI: 10.1007/bf01244818
|View full text |Cite
|
Sign up to set email alerts
|

Increased calcitonin gene-related peptide- and cholecystokinin-like immunoreactivities in spinal motoneurones after dorsal rhizotomy

Abstract: Possible changes in neuropeptides within the ventral horn of the spinal cord were investigated after unilateral dorsal rhizotomy at the lumbar level (L1-L6) in adult rats. Ten days after the surgery, immunohistochemical observations and radioimmunological determinations confirmed a marked loss of calcitonin gene-related peptide (CGRP)- and substance P (SP)-like immunoreactivities within the superficial layers of the deafferented dorsal horn, as expected from the degeneration of primary afferent fibres containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The present results indicate that unilateral lesioning of the dorsal root sensory input alone has only limited effect on peptide expression in the segmental motoneuron and then only in the acute postlesion survival period. This is in line with a study by Hirakawa and Kawata (1992), but somewhat in contrast to the finding by Taquet et al (1992), who reported a significant increase in the levels of CGW-LI in motoneurons 10 days after dorsal rhizotomy. In our study, CGRP-LI staining in the ventral horn was only increased 1 day postoperatively and this was seen bilaterally, while mRNA expression was up-regulated only ipsilaterally.…”
Section: Role Of Afference To the Rnotoneuronsupporting
confidence: 92%
“…The present results indicate that unilateral lesioning of the dorsal root sensory input alone has only limited effect on peptide expression in the segmental motoneuron and then only in the acute postlesion survival period. This is in line with a study by Hirakawa and Kawata (1992), but somewhat in contrast to the finding by Taquet et al (1992), who reported a significant increase in the levels of CGW-LI in motoneurons 10 days after dorsal rhizotomy. In our study, CGRP-LI staining in the ventral horn was only increased 1 day postoperatively and this was seen bilaterally, while mRNA expression was up-regulated only ipsilaterally.…”
Section: Role Of Afference To the Rnotoneuronsupporting
confidence: 92%
“…For example, increased CGRP-IR in motoneurons located in the ventral horn, the trochlear nucleus, the facial nucleus, and the hypoglossal nucleus have been reported following the transection of the sciatic (Arvidsson et al, 1990), trochlear (Wang et al, 1993), facial (Streit et al, 1989), and hypoglossal (Grothe, 1993) nerves, respectively. Increased CGRP-IR in ventral horn motoneu-Pons has also been reported following both ventral and dorsal root section (Hirakawa and Kawata, 1992) and dorsal root section alone (Taquet et al, 1992).…”
Section: Discussionmentioning
confidence: 74%
“…It has never previously been examined whether or not neuropeptide expression in motoneurons changes in response to irradiation, whereas these neurons have been extensively studied with respect to neuropeptide expression after other experimental situations. Thus, substantial changes in the levels of CGRP in spinal cord motoneurons are observed in response to axotomy (Arvidsson et al, 1990;Caldero et al, 1992), dorsal rhizotomy (Taquet et al, 1992), and spinal cord transection (Arvidsson et al, 1989;Marlier et al, 1990). Furthermore, the expression of several peptides is dramatically altered in spinal cord motoneurons after axotomy (Zhang et al, 1993).…”
Section: Discussionmentioning
confidence: 99%